2016
DOI: 10.18203/2320-6012.ijrms20160008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricaemia and essential hypertension: a case control study in Southern Rajasthan

Abstract: INTRODUCTIONLife is not merely to be alive, but to be healthy and wealthy. Despite incredible improvement in health since 1950, cardiovascular disease remains among the leading causes of death worldwide. Hypertension (HT) is the most common risk factor for cardiovascular morbidity and mortality. This positive relationship between blood pressure (BP) and cardiovascular risk has been shown to exist not only in those with higher BP but also in individuals with high-normal BP/prehypertension. 1 Prehypertension as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
1
1
3
Order By: Relevance
“…Lee Table-III al 15 reported majority of study cases of essential hypertension were in the range of 40-50 years, that is also in full agreement to the present study. However, age contradicts to a Pakistani study of Habib et al 14 has reported minimum age of 20 years that contradicts with the present study. Body weight and BMI 77.4±12.2 vs. 78.5±13.9 Kg (P=0.57) and 27.53±3.30 and 28.48±3.61 kg/ m 2 in control and cases respectively (P=0.0001).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Lee Table-III al 15 reported majority of study cases of essential hypertension were in the range of 40-50 years, that is also in full agreement to the present study. However, age contradicts to a Pakistani study of Habib et al 14 has reported minimum age of 20 years that contradicts with the present study. Body weight and BMI 77.4±12.2 vs. 78.5±13.9 Kg (P=0.57) and 27.53±3.30 and 28.48±3.61 kg/ m 2 in control and cases respectively (P=0.0001).…”
Section: Discussioncontrasting
confidence: 99%
“…The findings corroborate to the SUA in controls 2.91±0.75 vs. 5.70±1.76 mg/dl (P=0.0001) in the present study. Another previous study 14 reported similar findings of hyperuricemia in pre-hypertension and hypertension. This previous study reported SUA (mean± SD) of 4.91 ± 0.88 mg/dl in control, 5.89 ± 0.97 in pre-hypertension mg/dl and 6.56 ± 0.64 mg/dl in hypertension respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Some studies have reported association of hyperuricemia with systemic hypertension in women [7][8][9] , few in men 10 and others have reported this association in both genders. 11 A previous study 12 reported significant association of hyperuricemia and systemic hypertension in less than 40 years of age. While other studies 13,14 demonstrated contrasting occurrence in older than 40 years.…”
Section: Introductionmentioning
confidence: 93%
“…Penelitian di Kivu Selatan Republik Kongo dengan menggunakan 378 sampel, juga menemukan hasil yang sama. 7 Walaupun demikian, hasil berbeda ditemukan pada studi lainnya di beberapa lokasi berbeda seperti RSUD Sukoharjo 6 , Rajastan 5 , dan Banglades 17 , yang menemukan terdapat hubungan signifikan antara kejadian hiperurisemia dengan hipertensi.…”
Section: Pembahasanunclassified
“…Di mana, responden dengan hiperurisemia secara signifikan lebih tinggi pada kasus hipertensi. 5 Penelitian yang dilakukan oleh Umami pada tahun 2015 di RSUD Sukoharjo mendapatkan hasil bahwa sebanyak 50% sampel yang dilibatkan pada studi tersebut mengalami kondisi hiperurisemia. Hasil ini menunjukkan bahwa terdapat keterkaitan antara hiperurisemia dengan hipertensi pada subjek yang diteliti.…”
unclassified